A scoping review of cross-curricular models of Islamic content and English language - Ansyari, Muhammad Fauzan (Universitas Jambi, Indonesia, 2026)
This scoping review aims to provide an overview of research into religiously responsive cross-curricular models that integrate Islamic content and English language learning in Indonesia. Following a systematic review process, 21 selected articles were analyzed to understand curricular ideologies, representations, design approaches, quality criteria, and cross-curricular models. The findings reveal a predominant focus on intended curricula, particularly formal learning materials, and an instrumental approach to curriculum design. The review identifies diverse curricular ideologies, with a significant emphasis on social-reconstruction ideology aimed at fostering religious responsiveness through English instruction. Key quality criteria include internal consistency, relevance, and practicality. Despite the various cross-curricular models, the language-driven design is the most preferred. However, the review highlights gaps such as limited theoretical articulation, a narrow focus on intended curriculum, and a lack of longitudinal studies. These findings underscore the need for a more comprehensive approach to curriculum design that includes multiple levels of curriculum representation and considers both content and language integration holistically. Future research should focus on interdisciplinary collaboration, methodological diversity, and the practical application of instructional materials to enhance the effectiveness of integrated curricula.